CURRENT STATE AND PROGRESS OF CHILDREN›S TOURISM IN RUSSIAN FEDERATION - Ekaterina Vyacheslavovna Aigina; Nadezhda Igorevna Tulskaya (Sovremennye Issledovaniâ Socialʹnyh Problem, 2015)
Children’s tourism – one of the mass tourism types – carries out educative, academic, recreational and other social functions. It is one of the most consistent parts of tourist services market. In Russia, children’s tourism has significant social status and is regulated by a range of legal acts of federal and regional levels. Health and cultural tourism are the most developed and oldest segments of children’s tourism in our country. Educational programs are in stable demand as well. In recent decade there has been a significant change in the structure of demand for children’s recreation. Changes in socio-economic conditions in the post-Soviet period have led to the increased demand for municipal day camps and for specialized camps (sports, curative, etc.). Traditional children’s holiday camps became less popular. Every year the number of holiday camps in the countryside areas decreases. Now Krasnodar region, Altai region and Bashkortostan are the leaders in the number of pupils vacationing in the summer camps for children. Crimean Federal District has actively joined the system of children’s health tourism. The Black sea coast of Krasnodar region and the Crimea as well as Central Russia remain traditional Russian children’s holiday destinations for a long time. Children’s tours are highly seasonal and tied to school breaks and public holidays. Sightseeing programs nowadays have greatly expand their variety: there are a lot of entertaining, military, patriotic, educational routes. The Federal Program on children’s cultural tourism improvement has been worked out.